Absence of dynamic neural oscillatory response to environmental conditions marks childhood attention deficit hyperactivity disorder. (27th May 2022) - Arnett, Anne B.; Fearey, Margaret; Peisch, Virginia; Levin, April R.
Abstract : Background: Prior research suggests that symptoms of attention deficit hyperactivity disorder (ADHD) and related neurodevelopmental disorders may derive from alterations in the brain's ability to flexibly tune the balance between information integration and segregation and global versus local processing. This balance allows the brain to optimally filter salient stimuli in the environment and can be measured with electroencephalography (EEG) via calculation of the aperiodic spectral slope. A steeper aperiodic slope increases the capacity of global neural networks to process low‐salience stimuli, while a flatter aperiodic slope reflects an emphasis on local neural networks that respond preferentially to high‐salience input. Although aperiodic slope differences have been reported in ADHD, prior studies have not accounted for differing levels of stimulus input in experimental paradigms. There is evidence to suggest that dynamic shifts in neural oscillation patterns in response to changing environmental conditions could be critical for attention regulation. Methods: Using high‐density resting EEG, we measured aperiodic spectral slope during low contrast (lights off) and high contrast (lights on) environmental conditions in a sample of 88 7–11‐year‐old children diagnosed with ADHD and 29 controls (30% female). Results: While controls showed a flatter aperiodic slope during the high contrast (lights on) as compared to low contrast (lights off) environmental condition, children with ADHD did not show any change in aperiodic slope across conditions. Conclusions: This study presents a novel etiological model of biological mechanisms associated with ADHD. Children with ADHD show suboptimal modulation of intrinsic neural activity in response to changing environmental input. The dynamic spectral slope is a promising candidate biomarker for ADHD. The possibility that dynamic spectral slope is associated with cognitive‐behavioral regulation more broadly merits further investigation.